Identifikasi Boraks Dan Formalin Pada Bakso Daging Di Lingkungan Universitas Muhammadiyah Palangkaraya - Rabiatul Adawiyah (Anterior Jurnal, 2014)
Food security is the responsibility of all parties that is the government's responsibility as manager of government which includes order, security, and a prosperous society. The responsibilities of employers or manufacturers as the economic actors that drive business improvement and provide the needs of the community and the consumers who use the goods and services to meet their needs, especially food. The purpose of research is to determine the content of borax and formaldehyde in meatballs sold at the Muhammadiyah University of Palangkaraya. The method used is experimental research with laboratory approach that will be done with a series of try out. The results of this study show that meatballs in the environment of Muhammadiyah University of Palangkaraya partially detectable formaldehyde but largely undetectable contain formaldehyde as a hazardous material for Health. While the study of borax is undetectable contain borax, it indicated by the colour of the flame is not green, after the flame test there is no change of color on curcumin paper (still yellow) after the color test is done using curcumin paper.